Reverse-engineering 'esotericism': how to prepare a complex cultural concept for the cognitive science of religion - Asprem, Egil (Religion, 2016)
The article introduces a framework for preparing complex cultural concepts for the cognitive science of religion (CSR) and applies it to the field of Western esotericism. The research process (‘reverse engineering') rests on a building block approach that, after problematic categories have been deconstructed, seeks to reconstruct new scholarly objects in generic terms that can be operationalized in interdisciplinary contexts like CSR. A four-step research process is delineated, illustrated by a short discussion of previous work on ‘Gnosticism,' ‘magic,' and ‘religion,' before applying it to ‘esotericism.' It is suggested that the implicit scholarly objects of esotericism scholarship can be reconstituted in generic terms as concerned with processes of creating and disseminating ‘special knowledge.' Five definitional clusters are identified in the literature; these provide a basis for formulating research programs on the psychological and cognitive level, drawing on metarepresentational processes, event cognition, and psychological dispositions for altering experience.